3D printing of engineering materials: A state of the art review. (2020) - Singh, Tarunpreet; Kumar, Sanjeev; Sehgal, Shankar
Abstract: 3D printing or additive manufacturing is an engineering process used for producing a three-dimensional product layer-by-layer from a digital 3D model as per the requirement. This technique is fast-developing manufacturing technology. The growing demand for 3D printing is because of its advantages like rapid prototyping and producing customizable parts. These have been the key factors for its growth in the last three decades. The technique has now become one of the mainstream manufacturing processes. Numerous materials belonging to different classifications like metals, ceramics, polymers, composites and hybrids can be utilized for application in industries like automobile, aerospace, health care and medical, construction, electronics, food and many more. This review provides a basic understanding of the principles of the seven different techniques of 3D printing which are usually employed for fabricating a three-dimensional product. Furthermore the benefits of this technique are discussed. The need for further research is also identified here, by explaining the limitations of this technology in the current scenario.